Thermomechanical Solid Breeder Multiple-Effects Experiment (TESOMEX) with Volumetric Heating and FEM Benchmark Analysis. (3rd July 2020) - Lotfy, Mahmoud; Ying, Alice; Abdou, Mohamed; Lee, Dong Won; Ahn, Mu-Young
Abstract: Available experimental efforts on ceramic pebble beds and their associated constitutive equations are necessarily derived from single-effect tests where one parameter is varied and its effects are isolated and studied separately (e.g., using constant temperatures and externally applied loads). These experiments are incapable of reproducing the true multiple/synergistic effects of the physics that occur in real blankets, and the phenomena arising from the interactions of single effects are yet to be discovered. It is unclear whether the combined effect of plasticity and creep under reactor-relevant loading conditions will either enable the altered pebble bed packing configuration to reach an acceptable self-regulating temperature state or significantly deteriorate its heat transfer efficiency and subsequent tritium release. Therefore, studying the isolated thermal and mechanical effects is not sufficient to predict pebble bed behavior. It is the coupling and interdependence between the dynamic thermal and mechanical fields, as well as the synergistic effects between the various modes of deformation, that are key to fully understanding and predicting pebble bed behavior in a realistic fusion environment. However, previous mock-up experimental campaigns thus far have suffered from critical shortfalls that have severely hamstrung their scientific impact. The lack of experimental data that incorporate multiple-effects interactions in addition to the complexity of building a full-scale breeder unit mock-up triggered the need for this experimental effort. The body of work presented in this paper serves to (1) establish and validate the practicality of various volumetric heating simulation techniques for representative thermomechanical study, (2) recreate a prototypical breeder unit's thermal-hydraulic behavior using a scaled-down reduced-activation ferritic steel box with optimized manifold design, (3) evaluate the thermomechanical properties of the pebble bed using a novel nonintrusive in situ tactile-pressure-sensing technology capable of generating real-time contact pressure maps that reveal spatial and temporal stress evolution, and (4) develop and benchmark a thermomechanical finite element method code that is able to predict the pebble bed's thermomechanical evolution under the effects of creep and thermal cycling. The results of this study not only present novel experimental techniques and data that enhance our understanding of synergistic thermomechanical interactions and effects, but they also provide valuable data to serve as a basis for validation of the most recent pebble bed numerical models. Finally, it is worth mentioning that this work is part of a compendium around the Thermomechanical Solid Breeder Multiple Effects Experiment experimental campaign, known as TESOMEX. While this paper primarily focuses on novel heating and instrumentation techniques along with their opportunities and limitations, the other two papers shed more light on the prototypical thermomechanical evolution, pebble sintering, and possible modes of failure.